Cover Image. (23rd February 2018) - Fereidoonnezhad, Masood; Shahsavari, Hamid R.; Lotfi, Elaheh; Babaghasabha, Mojgan; Fakhri, Motahareh; Faghih, Zeinab; Faghih, Zahra; Hassan Beyzavi, M.
Abstract : The cover image, by Masood Fereidoonnezhad et al., is based on the Full Paper ( Benzyl isocyanide)gold(I) pyrimidine‐2‐thiolate complex: Synthesis and biological activity, DOI:10.1002/aoc.4200 . Design Credit: Eric Pipkin.